Eccentric exercise training: Modalities, applications and perspectives - Isner-Horobeti, M. E.; Dufour, S. P.; Vautravers, P.; Geny, B.; Coudeyre, E.; Richard, R. (Sports Medicine, 2013)
Eccentric (ECC) exercise is classically used to improve muscle strength and power in healthy subjects and athletes. Due to its specific physiological and mechanical properties, there is an increasing interest in employing ECC muscle work for rehabilitation and clinical purposes. Nowadays, ECC muscle actions can be generated using various exercise modalities that target small or large muscle masses with minimal or no muscle damage or pain. The most interesting feature of ECC muscle actions is to combine high muscle force with a low energy cost (typically 4- to 5-times lower than concentric muscle work) when measured during leg cycle ergometry at a similar mechanical power output. Therefore, if caution is taken to minimize the occurrence of muscle damage, ECC muscle exercise can be proposed not only to athletes and healthy subjects, but also to individuals with moderately to severely limited exercise capacity, with the ultimate goal being to improve their functional capacity and quality of life. The first part of this review article describes the available exercise modalities to generate ECC muscle work, including strength and conditioning exercises using the body`s weight and/or additional external loads, classical isotonic or isokinetic exercises and, in addition, the oldest and newest specifically designed ECC ergometers. The second part highlights the physiological and mechanical properties of ECC muscle actions, such as the well-known higher muscle force-generating capacity and also the often overlooked specific cardiovascular and metabolic responses. This point is particularly emphasized by comparing ECC and concentric muscle work performed at similar mechanical (i.e., cycling mechanical power) or metabolic power (i.e., oxygen uptake, V?O2). In particular, at a similar mechanical power, ECC muscle work induces lower metabolic and cardiovascular responses than concentric muscle work. However, when both exercise modes are performed at a similar level of V?O2, a greater cardiovascular stress is observed during ECC muscle work. This observation underlines the need of cautious interpretation of the heart rate values for training load management because the same training heart rate actually elicits a lower V?O2 in ECC muscle work than in concentric muscle work. The last part of this article reviews the documented applications of ECC exercise training and, when possible, presents information on single-joint movement training and cycling or running training programs, respectively. The available knowledge is then summarized according to the specific training objectives including performance improvement for healthy subjects and athletes, and prevention of and/or rehabilitation after injury. The final part of the article also details the current knowledge on the effects of ECC exercise training in elderly populations and in patients with chronic cardiac, respiratory, metabolic or neurological disease, as well as cancer. In conclusion, ECC exercise is a promising training modality with many different domains of application. However, more research work is needed to better understand how the neuromuscular system adapts to ECC exercise training in order to optimize and better individualize future ECC training strategies.